2012
DOI: 10.1186/1471-2164-13-268
|View full text |Cite
|
Sign up to set email alerts
|

Genome characterisation of the genus Francisella reveals insight into similar evolutionary paths in pathogens of mammals and fish

Abstract: BackgroundPrior to this study, relatively few strains of Francisella had been genome-sequenced. Previously published Francisella genome sequences were largely restricted to the zoonotic agent F. tularensis. Only limited data were available for other members of the Francisella genus, including F. philomiragia, an opportunistic pathogen of humans, F. noatunensis, a serious pathogen of farmed fish, and other less well described endosymbiotic species.ResultsWe determined the phylogenetic relationships of all known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
131
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(140 citation statements)
references
References 65 publications
9
131
0
Order By: Relevance
“…These functions include the oligopeptide transport and spermidine/putrescine biosynthesis (32,33), seven unique lipopolysaccharides (LPSs) that have been previously identified in F. tularensis but not in other Francisella species (13,63), and four restriction-modification (R-M) systems found in F. novicida (13,70).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These functions include the oligopeptide transport and spermidine/putrescine biosynthesis (32,33), seven unique lipopolysaccharides (LPSs) that have been previously identified in F. tularensis but not in other Francisella species (13,63), and four restriction-modification (R-M) systems found in F. novicida (13,70).…”
Section: Resultsmentioning
confidence: 99%
“…species (closest to). Recent attempts to conduct comparative genomic studies among members of the Francisella genus either have been conducted on only a few representatives (32,33,59), have focused on subspecies within F. tularensis (60,61), or have been conducted on incomplete, lower-quality draft genomes (62,63), where interpretation of relationships may be confounded by missing genetic features in the incomplete genomes.…”
mentioning
confidence: 99%
“…Because F. tularensis exhibits very little genetic variability, high-resolution analytical methods such as whole genome sequencing are appropriate for genetic typing in epidemiological investigations of tularaemia outbreaks and for source-tracing [29,30]. Initial canSNP analysis of the six included isolates revealed that they all belonged to the F. tularensis genetic clade B.12, which dominates in Europe between Scandinavia and the Black Sea [7,8,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…The genome sequences of strain U112, the clinical isolate 3523 (Australian strain) and Fx1 (Texas strain) are available, as well as some Ft. tularensis and F. philomiragia strains (Barabote et al, 2009;Beckstrom-Sternberg et al, 2007;Champion et al, 2009;Chaudhuri et 3 al., 2007;Larsson et al, 2005;Modise et al, 2012;Nalbantoglu et al, 2010;Petrosino et al, 2006;Rohmer et al, 2007;Siddaramappa et al, 2011;Sjodin et al, 2012;Zeytun et al, 2012). Ft. tularensis is a highly infectious zoonotic agent.…”
Section: Introductionmentioning
confidence: 99%